Awareness about ocular complications due to dental infections among dentists - A, SUBASHRI.; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2021)
Rare complications due dental infections injurious to the eye are ophthalmia, defective vision and blindness. These complications are many times neglected and not given much importance. There are no proper guidelines in preventing and managing the ocular problems.This study was done to assess the awareness among dentists about dental infection induced ocular complications. A self administered questionnaire was made and circulated among the participants. The sample size was 170 and the questionnaire was circulated through online means. The data was obtained and the results were tabulated using SPSS software. Only 37% participants were aware that dental infection can cause ocular complications. Textbooks and colleagues were the key sources of information. Majority of them showed interest in knowing the preventive and management methods.From this study, lack of knowledge and aptitude among the dentists about ocular complications was observed. Therefore further information must be provided and training must be given through workshops, camps.